Multiple Oral Ulcerations in a Seizure Patient with Undiagnosed Brain Arteriovenous Malformation - Astuti, Ambar Kusuma; Rahmayanti, Febrina (UI Scholars Hub, 2021)
Multiple ulcerations are rarely caused by a traumatic event, but seizures can induce repeated injury to the oral mucosa. A patient with a seizure history possesses a challenge in their dental management. Objective: In order to describe a case of multiple oral ulceration in a post-seizure patient with undiagnosed arteriovenous malformation (AVM) in the left parietal lobe and provide short guidelines for dentists in managing patient with a seizure history. Case report: A 23-years old female had multiple oral ulceration in the right and left buccal mucosa and her tongue. She reported having a seizure attack six days before. The patient never had a history of seizures or recurrent oral ulceration. During the seizure, improper placement of the spoon caused further damage to her oral mucosa. The trigger of her seizure is unknown. Based on the neurological consultation, she had an AVM on the left temporal lobe. In order to relieve pain, mouthwash containing aloe vera, sodium hyaluronate, glycyrhettinic acid, and polyvinylpyrrolidone (PVP) was prescribed. Conclusion: Dentists should be aware that oral mucosal injury can be related to a seizure disorder. A proper history and examination are essential to make an appropriate diagnosis. A safe dental treatment in seizure patients can be delivered accordingly.